2000
DOI: 10.1091/mbc.11.9.3045
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Redirection of Plasma Membrane Trafficking after Loss of Epithelial Cell Polarity

Abstract: In polarized Madin-Darby canine kidney epithelial cells, components of the plasma membrane fusion machinery, the t-SNAREs syntaxin 2, 3, and 4 and SNAP-23, are differentially localized at the apical and/or basolateral plasma membrane domains. Here we identify syntaxin 11 as a novel apical and basolateral plasma membrane t-SNARE. Surprisingly, all of these t-SNAREs redistribute to intracellular locations when Madin-Darby canine kidney cells lose their cellular polarity. Apical SNAREs relocalize to the previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 69 publications
(99 reference statements)
4
46
0
1
Order By: Relevance
“…The apical compartment identified in this study is not the vacuolar apical compartment (VAC) that was previously identified in nonpolarized epithelial cells (Vega-Salas et al, 1987Gilbert and Rodriguez-Boulan, 1991;Low et al, 2000). The apical structures we have described occur in normally growing cells that do not polarize (Fao and Clone 9) or in WIF-B cells before they become polarized.…”
Section: Apical Compartment Is Novelmentioning
confidence: 42%
“…The apical compartment identified in this study is not the vacuolar apical compartment (VAC) that was previously identified in nonpolarized epithelial cells (Vega-Salas et al, 1987Gilbert and Rodriguez-Boulan, 1991;Low et al, 2000). The apical structures we have described occur in normally growing cells that do not polarize (Fao and Clone 9) or in WIF-B cells before they become polarized.…”
Section: Apical Compartment Is Novelmentioning
confidence: 42%
“…Mechanistically, this linkage may reflect a requirement for WASp in the redistribution of essential soluble N-ethylmaleimide-sensitive factor attachment protein receptor machinery (SNARE) (30) to the effector synapse for cytokine-containing vesicle release. Indeed, loss of cellular polarity in epithelial cells leads to redistribution of target SNAREs to intracellular locations (31).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the evidence suggests that these genes also diverged similarly in function in each lineage, indicative of convergent evolution. Because these examples involve basic cellular machinery, they differ from gene duplications involving specialized tissuespecific machinery (e.g., syntaxins 1, 2, 3, and 4 and their plant equivalents, syp 111, 121, 131, and relatives) (48,49) and also from cases such as SSO1 and SSO2 in yeast, which encode plasma-membrane syntaxins with no discernable difference in function (50).…”
Section: 98/76/91/65mentioning
confidence: 99%